FERONIA-like receptor 1-mediated calcium ion homeostasis is involved in the immune response - Luo, Xiao; Wang, Long; Fu, Yuefeng; Liu, Qiqi; Chen, Ge; Liu, Yue; He, Wei; Gao, Aijun; Xu, Jingbo; Deng, Huafeng; Xing, Junjie (Frontiers in Plant Science, 2022)
Calcium (Ca2+) is the most abundant divalent cation in plants, and the levels Ca2+, a nutrient and secondary messenger, in cells have a critical role in plant immunity. Here, we found that FLR1 positively regulates Magnaporthe oryzae resistance and that the expression of FLR1 was strongly induced in response to Ca2+ deficiency. In addition, the Ca2+ content in the shoots of flr1 was lower than that in the wild type, and the M.oryzae-sensitive phenotype of the flr1 mutant was not rescued by exogenous application of Ca2+. Moreover, RNA sequencing (RNA-seq) revealed 2,697 differentially expressed genes (DEGs) in the flr1 mutant compared with the wild type, and the DEGs were involved in cellular metal ion homeostasis and transition metal ion homeostasis. The changes in the expression of overlapping genes between the flr1 mutant and the plants under low-Ca2+ treatment were in the same direction, indicating that FLR1 is involved in Ca2+ homeostasis. In summary, we found that FLR1 mediated resistance to M.oryzae, the phenomenon of which is associated with Ca2+ homeostasis.